(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effect of supplementation the ready to drink milk Metacare Opti on nutritional, digestive and health status of preschool children aged 36-59 months. Method: A controlled intervention study was completed in Ninh Binh province in September 2024 with 120 subjects. The intervention group (60 subjects) used formula supplementation Metacare Opti (a ready-to-drink) twice daily for 2 months and the control group (60 subjects) used a regular diet. The tool is calibrated and applies techniques standards for identifying the nutritional, digestive and health status and avoiding bias in research. Analyze data by SPSS20.0 software and describe by ratios and averages, use of appropriate statistical tools in biomedical research. Results: Results showed positive effects comparing the intervention group vs. the control group: Improved average weight: Weight was higher 0.58 kg (0.91 ± 0.31 kg vs. 0.33 ± 0.17 kg) with statistical significance (p<0.05). Average of height was higher 0.64 cm (1.59 ± 0.51cm vs. 0.95 ± 0.43 cm) with (p<0.05). Underweight malnutrition were lower 38.3% (p<0.05); the risk of malnutrition and malnutrition underweight were lower 38.4% (p<0.05); Stunting and the risk of stunting were lower 16,6% (p<0.05); wasting and the risk of wasting were lower 11.7% (p<0.05). The rate of respiratory infections redued 28.4% (p<0.05); diarrhoea redued 26.7%; constipation redued 20.0% (p<0.05); anorexia redued 36.6% (p<0.05); The digestive status was better, children had more easy to defecate, fecal soft and mold shaped increase by 21.6% (p<0.05). Conclusion: Supplementing twice daily of ready to drink milk Metacare Opti (360ml) in two months for children aged 36-59 months improved weight, height; had positive effects on digestion and health status with statistical significance (p<0.05).